Titania-loaded coal char as catalyst in oxidation of styrene with aqueous hydrogen peroxide - Nurhadi M.; Chandren S.; Yuan L.S.; Ho C.S.; Indra Mahlia T.M.; Nur H. (Walter de Gruyter GmbH, 2023)
Carbon; Catalysts; Coal; Hydrogen peroxide; Impregnation; Peroxides; Pyrolysis; Styrene; Sulfonation; Titanium dioxide; High selectivity; High surface area; Large pore volume; Loaded coals; Oxidation of styrene; Pyrolysis temperature; Short durations; Styrene oxidation; Oxidation